The Integrated Nutrition Education on eHealth Intervention and Its Effectiveness on Improvement of Anthropometric Status and Behavioural Outcomes of Obese Adults: A Systematic Review - Anggun Rusyantia; Ali Khomsan; Clara Meliyanti Kusharto; Hadi Pratomo (Amerta Nutrition, 2022)
Background: The problem of overnutrition has become an epidemic issue at the global level. As one of the effective ways to prevent and overcome obesity, nutrition education is growing by utilizing eHealth media as a message delivery channel.  Objectives: To identify studies that integrate nutrition education with eHealth-based technology in the prevention and control of obesity, behavioral theory and BCT (Behaviour Change Technique), their effectiveness in improving the anthropometric status and behavioral outcomes in obese adults. Discussion: Article searches were conducted using PubMed, Science Direct, ProQuest, and using manual search Google Scholar in reputable journals in the last ten years, and 17 English articles were obtained. Two forms of communication channels and activities were used to deliver nutrition education messages, namely interpersonal channels and internet-based mass media with or without assistance. Mobile applications were the most widely used as a messaging tool. The most frequently used theory was Social Cognitive Theory, and the majority of BCT were self-monitoring, goal setting, and feedback. The eHealth method (online) gave the same results on anthropometric status, physical activity, and treatment adherence compared to face-to-face (offline) by providing the same BCT-based obesity management intervention. Conclusions: Integrating nutrition education into eHealth media channels that emphasizes modification of eating behavior and physical activity has a significant effect on improving anthropometric status but was inconsistent on eating behavior and physical activity outcomes in adults with short-term intervention (≤3.5 months/ 14 weeks). This effect will give benefit the outcomes if followed by personal or group mentoring accompanied by well-design BCT.